PENERAPAN MANAJEMEN SUMBER DAYA MANUSIA DALAM PENINGKATAN KINERJA ACCOUNT REPRESENTATIVE DI KANTOR PELAYANAN PAJAK PRATAMA GRESIK - Gresika, Yaniar; Utari, Woro; Subijanto, Subijanto (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2023)
This study aims to knowing the performance of the Account Representative in KPP Pratama Gresik, to find out the implementation of human resource management in KPP Pratama Gresik. The research method used is qualitative with a case study approach. Data collection techniques by observation, interviews, and documentation. The data analysis technique used in this study is interactive analysis according to Miles and Hubberman, namely data reduction, data presentation and drawing conclusions or verification. The results of the study show that Account Representative performance is quite good by looking at the activities carried out when interacting directly with taxpayers or when working behind the scenes, The application of human resource management by the Head of the Office at KPP Pratama Gresik is carried out well, especially in terms of; HR placement, HR training and development, performance appraisal using qualitative and quantitative assessments. Meanwhile, compensation or allowances have been regulated separately in Presidential Regulation of the Republic of Indonesia Number 37 of 2015 concerning Employee Performance Allowances in the Directorate General of Taxes, but it is necessary to consider compensation which is the desire of the Account Representative not only in material form, but also through appreciation.Keywords: Account Representative, Management, Human Resources